Variation in parameters affecting risk of human disease due to TBE virus - Korenberg, E I; Kovalevskii YuV (Folia parasitologica, 1995)
To rank variables affecting risk of human disease due to tick-borne encephalitis (TBE) virus in the Russian Far East, we compared annual changes in (1) frequency of human contact with vector ticks, (2) prevalence of infection in the tick population and (3) quantity of virus present infected ticks. Sites were sampled uniformly over a 4-year period in a forested region where Ixodes persulcatus serves as the principle vector. The questing density of ticks on vegetation remained relatively constant during the course of this study. The frequency of contacts of the local human population with ticks carrying different doses of the TBE virus was changeable. The rate of TBE infection of humans in the study site corresponded to that of human contacts with highly infected ticks. The density of highly infected ticks represents the principal parameter for determining potential epidemiological significance of a natural TBE focus.
Keywords: Russia; Plants; klíště; Bites and Stings; Risk Factors; prevalence; Encephalitis Viruses, Tick-Borne; Arachnid Vectors; infestace klíšťaty; rostliny; Encephalitis, Tick-Borne; arachnida jako vektory; Animals; lidé; Humans; zvířata; klíšťová encefalitida; rizikové faktory; Rusko; Prevalence; kousnutí a bodnutí; Ixodes; Tick Infestations; viry klíšťové encefalitidy; pravděpodobnost; Probability